2014
DOI: 10.1016/j.jadohealth.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Multiple Sexual Partners From Adolescence Through Young Adulthood

Abstract: Purpose To examine time-varying associations between predictors of recent multiple sexual partners from middle adolescence through young adulthood. Methods We examined whether the odds of multiple partners in the past year were differentially predicted by substance use and depression over time, using data from a nationally representative longitudinal study (N=11,963, 52.2% female, 18.3% African American, 11.9% Hispanic, 3.5% Asian, 2.6% other race, M age at Wave 1=16.1 years, SD=1.8). Data were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 28 publications
4
70
0
1
Order By: Relevance
“…These models were then repeated to predict legal cynicism. Results are presented as figures because time-varying coefficients are estimated in continuous time leading to a number of coefficients too large to present in tables [62].…”
Section: Plan Of Analysesmentioning
confidence: 99%
“…These models were then repeated to predict legal cynicism. Results are presented as figures because time-varying coefficients are estimated in continuous time leading to a number of coefficients too large to present in tables [62].…”
Section: Plan Of Analysesmentioning
confidence: 99%
“…However, this questionnaire, developed for the teenage middle-and highschool population, with a mean age of 15.38 years, found that there is a difference in the sexuality of middle-school and high school students (Vasilenko & Lanza, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…[5][6][7][8] Studies conducted among adolescents have identified an association between substance use (eg, alcohol, marijuana, cocaine, and heroin) and sexual risk behaviors (SRBs) (eg, ever having sexual intercourse, having multiple sexual partners, not using a condom at last intercourse, and pregnancy before age 15 years), but there is a dearth of information on the association between NMUPD and SRBs among adolescents. [9][10][11][12][13][14][15][16][17] The few studies that exist focused on special populations such as homeless youth or were conducted in small geographic or clinical settings. [17][18][19] One such study surveyed sexually active adolescents and young adults aged 14 to 20 years in an emergency department setting and observed an association between each class of prescription drugs (stimulants, opioids, and sedatives) and SRBs.…”
mentioning
confidence: 99%